2016
DOI: 10.1016/j.sleep.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the first-line treatment of restless legs syndrome/Willis–Ekbom disease, prevention and treatment of dopaminergic augmentation: a combined task force of the IRLSSG, EURLSSG, and the RLS-foundation

Abstract: A Task Force was established by the International Restless Legs Syndrome Study Group (IRLSSG) in conjunction with the European Restless Legs Syndrome Study Group (EURLSSG) and the RLS Foundation (RLS-F) to develop evidence-based and consensus-based recommendations for the prevention and treatment of long-term pharmacologic treatment of dopaminergic-induced augmentation in restless legs syndrome/Willis-Ekbom disease (RLS/WED). The Task Force made the following prevention and treatment recommendations: As a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
201
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 266 publications
(222 citation statements)
references
References 47 publications
4
201
0
17
Order By: Relevance
“…This study reported that gabapentin enacarbil (1200 mg/ completely but to ensure that they do not interfere with quality of life. 153 If symptoms become bothersome, the dose can be increased cautiously, but this will increase the risk of development of augmentation. 153 A non-dopaminergic agent can be added if concerns about the dose of the dopaminergic drug occur.…”
Section: Rotigotinementioning
confidence: 99%
“…This study reported that gabapentin enacarbil (1200 mg/ completely but to ensure that they do not interfere with quality of life. 153 If symptoms become bothersome, the dose can be increased cautiously, but this will increase the risk of development of augmentation. 153 A non-dopaminergic agent can be added if concerns about the dose of the dopaminergic drug occur.…”
Section: Rotigotinementioning
confidence: 99%
“…Given the high risk of augmentation with dopaminergic medications, a calcium channel α2δ ligand is often preferred over dopamine agonists for long-term therapy 4. New guidelines were published in 2016 for the first-line treatment of RLS and prevention of dopaminergic augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…New guidelines were published in 2016 for the first-line treatment of RLS and prevention of dopaminergic augmentation. These guidelines encourage the use of calcium channel α2δ ligands as first-line treatment in RLS over dopamine agonist 4. A dopamine agonist can be still used as first-line therapy but requires close follow-up to identify early signs of augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…One international guideline suggests the prevention of augmentation from the outset, by initiating RLS treatment in de novo patients with non-dopaminergic drugs, such as a2d ligands [41]; however, these options are not always available (e.g. the a2d ligand gabapentin enacarbil is not currently approved for RLS treatment in the EU [4,41]). Longer-acting dopamine receptor agonists at lower dosages have a lower likelihood of causing augmentation [1,3].…”
Section: 3)mentioning
confidence: 99%
“…5). The use of rotigotine is recommended as an option in cases of augmentation, although the guideline states that long-term treatment with rotigotine at higher dosages may also result in augmentation [41].…”
Section: 3)mentioning
confidence: 99%